Knowledge Transfer ‘Mapalus’ in An Eris Village, Indonesia - Ventje A. Senduk (AIBPM Publisher, 2018)
In this article, the authors present an examination of Mapalus, a traditional management related to knowledge transfer deeply embedded in the lives of families in Minahasa, Indonesia. The main goal of this study is to detail the extent to which knowledge transfer between generations (known as Mapalus) has shifted from the noble meaning of Mapalus. Data were collected using direct observations and informal in-depth interviews. After the process of collecting data, the data were analyzed and validated using triangulation. The major research location was Eris Village, Minahasa. Eris Village is one of the areas in Minahasa known for its agricultural products. The research was conducted in six months period. While Mapalus does not in principle involve monetary exchanges, the current practice of Mapalus shows that it does involve monetary exchanges. This is argued to have been facilitated by parents’ expectation of their children to work in the city rather than continue the practice of Mapalus. Considering that Mapalus is theorized to improve entrepreneurial activities in the area, implications for entrepreneurship and economic development are discussed. Keywords: Agriculture, Entrepreneurship, Knowledge Transfer, Mapalus